The synthesis and properties of some polymer hydrogels - Hird, Bryn (Rhodes University, Faculty of Science, Department of Chemistry, 1984)
The interactions between water molecules and polyelectrolyte species in aqueous solutions are reviewed and are used to infer interactions occuring in swollen crosslinked polyelectrolyte hydrogels. Linear poly(acrylic acid ) and derivatives neutralised to varying degrees with alkali-metal hydroxides are prepared and characterised. Samples of these compounds are crosslinked by 'Y - irradiation to form hydrogels. Hydration studies on linear polymers, crosslinked material and a commercial polyacrylate hydrogel indicate a possible hydration structure and provide some insight into the nature of water-polymer interactions within a sHollen polyacrylate gel.,KMBT_363,Adobe Acrobat 9.53 Paper Capture Plug-in
Keywords: Colloids